DEFINING OF COMPUTER PROGRAMS AS AN OBJECT OF INTELLECTUAL PROPERTY LAW AND THE LEGAL BASIS OF PROTECTION - Грабовська, Ганна Миронівна; Семенюк, Ярина Андріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Objective: to define the term «computer program», to explore the structure and elements of computer programs as objects of intellectual property rights and their legal protection. Research methods: logical, formal-dogmatic, comparative-legal, etc. Results: definition of the term «computer program», investigation of the structure and elements of computer programs as objects of intellectual property rights and their legal protection on the basis of these research methods. Discussion: many scientists are currently discussing intellectual property issues for computer programs and looking for ways to solve them. Such an object of legal protection, as a computer program, needs special attention, since neither the protection of a computer program as an object of copyright by analogy with a literary work, nor the protection of a computer program by a patent, provide the full and necessary level protection and confidence in the integrity and inviolability of the owner of his rights. This facility has its own peculiarities and complexity to protect, and therefore legislation must evolve as these technologies evolve. Due to the rapid development of the latest technologies, the legal protection of computer programs and software is especially relevant today. The current legislation does not fully take into account all the features of such an object of protection as computer programs, which leads to infringement of the rights of the owners and users of this object of intellectual property rights. The complexity of protecting computer programs lies in the complex nature of this object of legal protection. Although a computer program can be considered as an integral object, it should be noted that a large number of elements are components of this object. The issue of legal protection of software is actively discussed not only at the national level but also in the international arena.